The impact of training load on bone mineral density of adolescent swimmers: A structural equation modeling approach - Ribeiro Agostinete, R.; Maillane-Vanegas, S.; Lynch, K. R.; Turi-Lynch, B.; Coelho e Silva, M. J.; Zapaterra Campos, E.; Ungari Cayres, S.; Araujo Fernandes, R. (Pediatric Exercise Science, 2017)
Purpose: To investigate the mediating effect of muscle mass on the relationship between training load and bone density in adolescent swimmers. Methods: A cross-sectional study involving 87 control and 22 swimmers aged 10-19 years (overall sample: n=109). Swimmers had a minimum of 1 year of competition in regional and national championships, and control adolescents reported 1 year without any organized sport. Bone density was the main outcome (dual-energy X-ray absorptiometry), which was measured in upper limbs, lower limbs, spine, and whole body. Monthly training load was the independent variable, while the mediation effect of lean soft tissue was assessed. Maturity offset, age, inflammation, and vitamin D intake were treated as covariates. Results: Swimmers had lower bone density than controls; there was a significant and positive relationship between training load and muscle mass. In boys, training load presented a negative correlation with bone density in lower limbs [r=-.293; 95% confidence interval (CI), -.553 to -.034]. In girls, training load was negatively related to bone mineral density in lower limbs (r=.563; 95% CI, -.770 to -.356) and whole body (r=-.409; 95% CI, -.609 to -.209). Conclusion: Training load had a negative relationship on bone density of swimmers of both sexes, independently of the positive effect of lean soft tissue on bone density.